Statistical Aspects of Legal Terms In The General Dictionaries of Uzbek Language (Zien Journal of Social Sciences and Humanities, 2021)
Terminological units related to jurisprudence (legal and legal pometal) in the explanatory dictionaries of the Uzbek language are analyzed according to the semantic field, morphological and derivational features in the article. Based on the analysis and statistical description, comments are made on the formation of terms, their pometal use in dictionaries, the selection of the total number of terms in the dictionary by semantic groups. It is concluded that the statistical method can be used to draw conclusions about the development of language units, in particular, the statistics of legal terms in the glossary